The first Triassic beaded lacewing (Neuroptera: Berothidae) from Central Asia, with redescription of Mesoberotha superbа (Riek, 1955) - Khramov, Alexander V. (Zootaxa, 2023)
Ferganoberotha minutissima gen. et sp. nov. (Berothidae) is described from the Middle-Late Triassic Madygen Formation (Kyrgyzstan) based on an isolated forewing. This is the first species of Triassic Berothidae to be reported from Eurasia. Mesoberotha superbа (Riek, 1955), the type genus of Mesoberothidae from the Late Triassic of Australia, is redescribed and transferred to Berothidae, thereby making the former family a junior synonym of the latter.